FAIRNESS 2016. (August 2016) - Unknown
Abstract : FAIRNESS 2016 was the fourth edition in a series of workshops designed to bring together excellent international young scientists with research interests focused on physics at FAIR (Facility for Antiproton and Ion Research) and was held on February 14-19 2016 in Garmisch-Partenkirchen, Germany. The topics of the workshops cover a wide range of aspects in both theoretical developments and current experimental status, concentrated around the four scientific pillars of FAIR. FAIR is a new accelerator complex with brand new experimental facilities, that is currently being built next to the existing GSI facility close to Darmstadt, Germany. The spirit of the conference is to bring together young scientists, e.g. young non-tenured scientists, postdocs and advanced PhD students to present their work, to foster active informal discussions and build up networks. Every participant in the meeting with the exception of the organizers gives an oral presentation, and all sessions are followed by an hour long discussion period. During the talks, questions are anonymously collected in a box to stimulate discussions. The broad physics program at FAIR is reflected in the wide range of topics covered by the workshop: Atomic and plasma physics, biophysics, material sciences and applications Nuclear structure, astrophysics and reactions Physics of hot and dense nuclear matter, QCD phase transitions and critical point Hadron Spectroscopy, Hadrons in matter and Hypernuclei Experimental programs APPA, CBM, HADES, PANDA, NUSTAR, as well as BES, NICA and the RHIC beam energy scan For these different areas one invited speaker was selected to give a longer introductory presentation. The write-ups of the talks presented at FAIRNESS 2016 are the content of this issue of Journal of Physics: Conference Series and have been refereed according to the IOP standard for peer review. This issue constitutes therefore a collection of the forefront of research that is dedicated to the physics at FAIR. June 2016, Organizers of FAIRNESS 2016: Marco Destefanis, Tetyana Galatyuk, Fernando Montes, Diana Nicmorus, Claudia Ratti, and Laura Tolos.